Increased Consumption of Fruit and Vegetables Is Related to a Reduced Risk of Cognitive Impairment and Dementia: Meta-Analysis - Jiang, Xian; Huang, Jiang; Song, Daqiang; Deng, Ru; Wei, Jicheng; Zhang, Zhuo (Frontiers in Aging Neuroscience, 2017)
Background: Increased consumption of fruit and vegetables has been shown to be associated with a reduced risk of cognitive impairment and dementia in many epidemiological studies. The purpose of this study was to assess the strength of this association in a meta-analysis. Methods: We identified relevant studies by searching Medline, Embase, and Cochrane Library electronic databases (from 1970 to January 2016). Study were included if they reported relative risks and corresponding 95% confidence intervals (CIs) of cognitive impairment and dementia with respect to frequency of fruit and vegetable intake. Results: Nine studies (5 cohort studies and 4 cross-sectional studies) met the inclusion criteria and were included in the meta-analysis. There were a total of 31,104 participants and 4,583 incident cases of cognitive impairment and dementia. The meta-analysis showed that an increased consumption of fruit and vegetables was associated with a significant reduction in the risk of cognitive impairment and dementia (OR=0.80, 95% CI 0.71-0.89). Subgroup analysis indicated this inverse association was only found among participants with mean age over 65 years and combined sexes. Dose-response meta-analysis showed that an increment of 100 g per day of fruit and vegetable consumption was related to an approximately 13% (OR=0.87, 95% CI 0.77-0.99) reduction in cognitive impairment and dementia risk. There was no potential publication bias in the meta-analysis and the dose-response meta-analysis. Conclusions: The increased consumption of fruit and vegetables is associated with a reduced risk of cognitive impairment and dementia.